Kebijakan Pemerintah Daerah di Bidang Pertanian dalam Hubungan dengan Desentralisasi di Kabupaten Timor Tengah Utara - Yohanes Pebrian Vianney Mambur (Fakultas Pertanian, Universitas Timor, 2017)
Research on government policy in the agriculture sector in relation to decentralization in Regency of Timor Tengah Utara is an empirical research. This research aims to improve government policies in relation to decentralization, so that local governments do not abuse their authority in issuing the policy especially in the mining policy. This research uses sociological and ecological approach to assist local governments in issuing the policy so that policies can prosper the people. Results from this research are: To design symmetric decentralization to asymmetric decentralization. The design of asymmetric decentralization is used because a uniform decentralized model ignores the fact that the area has a level of maturity, the coverage area, the potential of the area and population that varies between one and the other. Uniform decentralization model also complicate the region in the developing bureaucratic structures. Make the agricultural sector as a mandatory affair of the government of North Central Timor Regency. Local government policy should be based on the study of sociology ecology.